Attitude of undergraduate medical students towards teaching learning process during their course in a teaching hospital of South Kerala - Nelson, Vincy; Stephen, Sabu; Simon, Sony (International Journal Of Community Medicine And Public Health, 2021)
Background: Student’s perception of the learning environment where they study has shown significant impact on their behavior level and academic level. The aim of the study was to find out the student’s perception of their learning environment in an Indian medical school of South Kerala and to study differences in perceptions between years of study, gender. Methods: In this study we used the Dundee Ready Education Environment Measure (DREEM) inventory which was administered to undergraduate medical students of first (N=100), second (N=92), third (N=62) and fourth years (N=75) of Travancore Medical College, Kollam. Scores obtained were expressed as mean±standard deviation (SD) and analyzed using one-way ANOVA and post hoc test was used. Results: A total of 400 students were studying in our medical college. Among them 330 students became participants of the study. Males comprised of 116 (35.2%) and females 214 (64.8%). Students less than 21 years was 200 (60.6%) and above 21 years 130 (39.4%). Final year MBBS students scored well when compared with the first years and second years. Post hoc analysis also showed same results. Significant relation between Student’s Perception of Learning, SPoT (value=0.001); Student’s Academic Self-Perception, SPoA (p value=0.022), SPoA (p value=0.010); and SSSP (p value=0.016) between batches has been observed. There was significant difference between males and females in the perception of atmosphere and was found to be statically significant. Conclusions: In this study the student’s perceptions of educational environment showed that the student’s enthusiasm improved as they move across years and was statically found to be significant. In the sub category student’s perception on atmosphere there was significant difference between males and females and it was statically found to be significant (p value less than 0.05).